2017
DOI: 10.1016/j.jcjo.2017.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of reasons for noncompliance with laser treatment in patients of diabetic retinopathy

Abstract: Objective-To identify the underlying reasons for noncompliance among Chinese patients undergoing laser photocoagulation treatment for diabetic retinopathy (DR). Design-Prospective cohort study.Participants-A total of 262 patients with DR with indications for panretinal photocoagulation and focal laser treatment were recruited.Methods-Those who did not complete the prescribed laser treatment were categorized into 2 types of defaulters: Type 1 defaulters were those who did not initiate laser treatment as schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…Studies of DR services in Pakistan, Oman and China reported that 29.5%, 22.8% and 27.9% of patients respectively did not initiate treatment. [7][8][9] In the study in China, an additional 17.6 % did not complete the treatment course, for reasons including being unaware of the importance of treatment and the need to complete the full course, and fear of treatment. 9 In high-income countries the proportion of patients not completing treatment tends to be lower than in low-income countries but still signi cant.…”
Section: Rapid Review Registration: Osf: Osfio/h5wgrmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of DR services in Pakistan, Oman and China reported that 29.5%, 22.8% and 27.9% of patients respectively did not initiate treatment. [7][8][9] In the study in China, an additional 17.6 % did not complete the treatment course, for reasons including being unaware of the importance of treatment and the need to complete the full course, and fear of treatment. 9 In high-income countries the proportion of patients not completing treatment tends to be lower than in low-income countries but still signi cant.…”
Section: Rapid Review Registration: Osf: Osfio/h5wgrmentioning
confidence: 99%
“…[7][8][9] In the study in China, an additional 17.6 % did not complete the treatment course, for reasons including being unaware of the importance of treatment and the need to complete the full course, and fear of treatment. 9 In high-income countries the proportion of patients not completing treatment tends to be lower than in low-income countries but still signi cant. A review in the USA reported that approximately 15% of patients didn't initiate treatment and 15% of those didn't complete it.…”
Section: Rapid Review Registration: Osf: Osfio/h5wgrmentioning
confidence: 99%
“…In some communities with limited access to eye care, TMDRS is often the only chance for patients to be evaluated, and image quality requirements are higher. A few studies [15][16][17] have found low adherence to referral recommendations for ophthalmological care among patients discovered to have sight-threatening disease, regardless of availability and cost of treatment resources. Arguably, this finding would mean that patient engagement in future treatment and diabetes control needs to begin earlier, before severe retinal disease is present.…”
Section: Validation Of Handheld Devicesmentioning
confidence: 99%
“…Studies of DR services in Pakistan, Oman and China reported that 29.5%, 22.8% and 27.9% of patients respectively did not initiate treatment. [7][8][9] In the study in China, an additional 17.6 % did not complete the treatment course, for reasons including being unaware of the importance of treatment and the need to complete the full course, and fear of treatment. 9 In high-income countries the proportion of patients not completing treatment tends to be lower than in low-income countries but still significant.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In the study in China, an additional 17.6 % did not complete the treatment course, for reasons including being unaware of the importance of treatment and the need to complete the full course, and fear of treatment. 9 In high-income countries the proportion of patients not completing treatment tends to be lower than in low-income countries but still significant. A review in the USA reported that approximately 15% of patients didn't initiate treatment and 15% of those didn't complete it.…”
Section: Introductionmentioning
confidence: 99%